Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T20:22:51+01:00
A) a + (a-b) = a + a - b = 2a-b

b) 2x - (x+4) = 2x - x -4 = x-4

c) 7 - (-x + 6) = 7 + x -6 = x+1

d) - (x+4) + (x-5) = -x- 4 + x- 5 = -9

e) 1 - (t+p) - (t-2) = 1 -t -p -t + 2 = -p +3

f) - (-y+2) + (-2y - 4) = y -2 -2y -4 = -y-6
2010-01-27T20:24:37+01:00
2010-01-27T20:27:36+01:00
Nie wiem jaki to materiał ale takie działania też mam więc chyba dobrze będzie:)
a) a + (a-b) = 2a + 1b
b) 2x - (x+4) = 3x - 4
c) 7 - (-x + 6) = 1 + 1x
d) - (x+4) + (x-5) = 2x - 9
e) 1 - (t+p) - (t-2) = 3 + 2t - 1p
f) - (-y+2) + (-2y - 4) = -1y - 6